Rationale for Antioxidant Supplementation in Sarcopenia - Francesco Cerullo; Giovanni Gambassi; Matteo Cesari (Journal of Aging Research)
Sarcopenia is an age-related clinical condition characterized by the progressive loss of motor units and wasting of muscle fibers resulting in decreased muscle function. The molecular mechanisms leading to sarcopenia are not completely identified, but the increased oxidative damage occurring in muscle cells during the course of aging represents one of the most accepted underlying pathways. In fact, skeletal muscle is a highly oxygenated tissue and the generation of reactive oxygen species is particularly enhanced in both contracting and at rest conditions. It has been suggested that oral antioxidant supplementation may contribute at reducing indices of oxidative stress both in animal and human models by reinforcing the natural endogenous defenses. Aim of the present paper is to discuss present evidence related to possible benefits of oral antioxidants in the prevention and treatment of sarcopenia.